Self-Defending towards Bullying in the Novel The Nerd can Fight - Pakaya, Asriyani; Baga, Magdalena; Muhamad, Farid (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Lack of affection from both parents and also the loss of someone who is deeply loved can cause someone to withdraw from social interactions. Someone who withdraws from social interactions, especially teenagers, can result in them becoming victims of bullying. The consequences of this bullying can have an impact on the victim’s mental health. This study aims to describe the types of bullying experienced by Cassandra, the main character in the novel The Nerd Can Fight. This study uses the theory of personality structure by Sigmund Freud and a psychoanalytic/psychological approach. Due to the death of her brother, Cassandra feels lost, guilty, traumatized, and upset, so she withdraws more from her friends. The results of the study concluded that three types of bullying in the novel The Nerd Can Fight, namely verbal bullying, physical bullying, and mental or psychological bullying experienced by the main character, Cassandra; she can defend herself against it by avoiding conflict, not responding to the bullying, not caring, and being indifferent.This attitude arises because she has a role model, namely her brother, and the presence of her best friend, Adam, makes the main character, Cassandra, able to defend herself from bullying.